Challenges and opportunities for enhancing sustainable cowpea production: proceedings of the World Cowpea Conference III held at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, 48 September 2000 - Fatokun, C.A.; Tarawali, Shirley A.; Singh, B.B.; Kormawa, P.M.; Tamo, Manuele (2002)
A number of recent studies have added further information on the genetics of important traits in cowpea. These include inheritance of qualitative traits such as plant pigmentation; flower colour, seed colour, seed coat texture, resistance to rust, scab, smut, nematode, severe mosaic virus, Striga, Alectra, aphid, bruchid, heat, drought tolerance, and male sterility and quantitative traits such as protein content, seed size, seed yield, and fodder quality. A few studies on linkage and mapping have also been conducted. The gene symbols from recent studies and earlier reports have been collated in a classified trait-based gene index for easy reference. While reviewing the past genetic work, obvious gaps needing further studies have been indicated.